Effective and Facile Determination of Vitamin B6 in Human Serum with CuO Nanoparticles/Ionic Liquid Crystal Carbon Based Sensor. Issue 13 (8th November 2017) - Atta, Nada F.; Galal, Ahmed; El-Ads, Ekram H.; El-Gohary, Asmaa R. M.
Abstract : New insights in fabrication of a sensitive, carbon nanotubes-based electrochemical sensor for determination of vitamin B6 (PY) are presented in this work. This was achieved by exploring the interesting properties of a conductive composite based on manual casting of successive layers of carbon nanotubes mixed with ionic liquid crystal and CuO nanoparticles (GC/(ILC-CNTs)/CuO) over glassy electrode surface. The proposed sensor was successfully used for the simultaneous determination of binary mixtures of PY and other vitamins (B2, B9, B12 or C) with good resolution. Under optimized conditions, a linear calibration curve was obtained for the determination of vitamin B6 in blood serum within the range 0.5 μmol L −1 to 50 μmol L −1 with sensitivity of 877 μA/mmol L −1, detection limit of 3.09 nmol L −1 and limit of quantification 10.31 nmol L −1 . Furthermore, the recovery results of real blood serum samples proved excellent using the proposed composite which makes it a potential candidate for PY routine analysis.